2016
DOI: 10.1038/srep22699
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of Porous NiCo2O4 Microspheres: Application as High Performance Asymmetric and Symmetric Supercapacitors with Large Areal Capacitance

Abstract: Large areal capacitance is essentially required to integrate the energy storage devices at the microscale electronic appliances. Energy storage devices based on metal oxides are mostly fabricated with low mass loading per unit area which demonstrated low areal capacitance. It is still a challenge to fabricate supercapacitor devices of porous metal oxides with large areal capacitance. Herein we report microwave method followed by a pyrolysis of the as-prepared precursor is used to synthesize porous nickel cobal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(80 citation statements)
references
References 60 publications
8
71
0
1
Order By: Relevance
“…For quantitative considerations, the specific capacitance was calculated as follows: In the three-electrode measurement, the specific capacitance is calculated from charge-discharge profiles using the following equation: Cs=(I×t)/(V×m) For two electrodes symmetric system the following equation is used to calculate the specific capacitance: Cs= 2×I×dt/m× ΔV [22] Where Cs (F/g) is specific capacitance of the supercapacitor, I (A) corresponds to the discharge current, ΔV (V) is the potential window, Δt(s) is the discharge time, and m (g) refers to the mass of active materials on the one electrodes. For quantitative considerations, the specific capacitance was calculated as follows: In the three-electrode measurement, the specific capacitance is calculated from charge-discharge profiles using the following equation: Cs=(I×t)/(V×m) For two electrodes symmetric system the following equation is used to calculate the specific capacitance: Cs= 2×I×dt/m× ΔV [22] Where Cs (F/g) is specific capacitance of the supercapacitor, I (A) corresponds to the discharge current, ΔV (V) is the potential window, Δt(s) is the discharge time, and m (g) refers to the mass of active materials on the one electrodes.…”
Section: Fabrication Of All Solid-state Supercapacitor Electrodesmentioning
confidence: 99%
“…For quantitative considerations, the specific capacitance was calculated as follows: In the three-electrode measurement, the specific capacitance is calculated from charge-discharge profiles using the following equation: Cs=(I×t)/(V×m) For two electrodes symmetric system the following equation is used to calculate the specific capacitance: Cs= 2×I×dt/m× ΔV [22] Where Cs (F/g) is specific capacitance of the supercapacitor, I (A) corresponds to the discharge current, ΔV (V) is the potential window, Δt(s) is the discharge time, and m (g) refers to the mass of active materials on the one electrodes. For quantitative considerations, the specific capacitance was calculated as follows: In the three-electrode measurement, the specific capacitance is calculated from charge-discharge profiles using the following equation: Cs=(I×t)/(V×m) For two electrodes symmetric system the following equation is used to calculate the specific capacitance: Cs= 2×I×dt/m× ΔV [22] Where Cs (F/g) is specific capacitance of the supercapacitor, I (A) corresponds to the discharge current, ΔV (V) is the potential window, Δt(s) is the discharge time, and m (g) refers to the mass of active materials on the one electrodes.…”
Section: Fabrication Of All Solid-state Supercapacitor Electrodesmentioning
confidence: 99%
“…However, the atypical architectures fabricated from hard template and through two-step synthetic strategies mostly suffering from their high cost and tedious synthetic procedures [19][20][21][22][23][24][25]. So it is highly desirable to develop one-pot synthesis of novel inorganic materials without templates and to explore their multifunction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the XRD studies have confirmed the complexation of GO as rGO localized in the ZAP matrix. The conformation envelope of ZAPG2 yielded a smaller crystallite size of 32.2 nm than ZAP (69.2 nm) (Debye–Scherrer relation), paving the way for the improved electrochemical performance of ZAPG2 compared to that of the pure ZAP …”
Section: Resultsmentioning
confidence: 99%